A Simplified Waveform Energetics Approach to Interpreting Arterial and Venous Pressure. Issue 27 (2018) - Davidson, Shaun M.; Balmer, Joel; Pretty, Chris; Desaive, Thomas; Chase, J. Geoffrey
Abstract: This paper develops a novel methodology for extracting simple, beat-to-beat, lumped metrics of systemic circulation performance by comparing the catheter pressure waveforms from the femoral artery and vena cava. Their diagnostic potential is compared to the similar, clinically used metric ΔMP, the drop in mean blood pressure between the aorta and vena cava, across an experimental cohort encompassing the progression of sepsis and several clinical interventions known to alter circulatory state. Both Ofe →vc, the model derived pressure attenuation between the femoral artery and vena cava, and the clinical metric, ΔMP, performed well. However, Ofe →vc reduced the optimal average time to sepsis detection from endotoxin infusion from 46.2 minutes for ΔMP to 11.6 minutes, for a slight increase in false positive rate from 1.8% to 6.2%. Thus, the potential diagnostic benefits of this novel approach are demonstrated, and a case is made for further investigation.